2005 European Conference on Power Electronics and Applications 2005
DOI: 10.1109/epe.2005.219492
|View full text |Cite
|
Sign up to set email alerts
|

Sensorless control of PM synchronous motors and brushless DC motors - an overview and evaluation

Abstract: This paper provides a review of the literature addressing sensorless operation methods of PM brushless machines. The methods explained are state-of-the-art of open and closed loop control strategies. The closed loop review includes those methods based on voltage and current measurements, those methods based on back emfmeasurements, and those methods based on novel techniques not included in the previous categories. The paper concludes with a comparison table including all main features for all control strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 22 publications
(27 reference statements)
0
6
0
Order By: Relevance
“…By (10), this load angle oscillation makes the I-F method torque T e oscillation too. A LPF is introduced in this subsection to smooth I-F input signal.…”
Section: A Speed Command Analysismentioning
confidence: 97%
See 2 more Smart Citations
“…By (10), this load angle oscillation makes the I-F method torque T e oscillation too. A LPF is introduced in this subsection to smooth I-F input signal.…”
Section: A Speed Command Analysismentioning
confidence: 97%
“…The second one is the torque current should be smooth at switch process. By comparing (10) and (19), it can be found that, the torque jump is proportioned to the switch load angle θ LS .…”
Section: Startup Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…The flux position is estimated from the measured current and voltages which are then manipulated and used to control the switching angle of the power electronics. Many types of flux observer have been discussed in papers and books [15][16][17][18][19][20]. In general, the steady-state first derivative of the angle gives the speed.…”
Section: Over-threshold Speed Controlmentioning
confidence: 99%
“…All the solutions proposed during the last years have both advantages and drawbacks. Reference [3] gives a state of art of sensorless techniques for both PMSM and BLDC motor. Those for PMSM are generally based on algebraic manipulation of motor equations using voltage and current measurements.…”
Section: Introductionmentioning
confidence: 99%